A marine geophysical study of the Wilkes Land rifted continental margin, Antarctica - Close, D; Watts, A; Stagg, H (2009)
The Wilkes Land margin of East Antarctica, conjugate to the southern Australian margin, is a non-volcanic rifted margin that formed during the Late Cretaceous. During 2000-01 and 2001-02, Geoscience Australia acquired ∼10000 line km of seismic reflection and refraction, magnetic anomaly and gravity anomaly data over the margin. We have used the seismic data to estimate the sediment thickness along the margin. The data reveal a deep (>11 km) rift basin that contains over 9 km of sediments seaward of the Totten Glacier, western Wilkes Land. The limits of oceanic and continental crust that underlies the thick post-rift and the significantly thinner pre- and syn-rift sediments are equivocal. Seismic reflection data suggest a 30-100 km wide continent-ocean transition zone (COTZ) along the margin. The COTZ extends over 400 km seaward of the shelf break off the eastern Wilkes Land/Terre Adélie sector of the margin. This seaward salient, referred to here as the Adélie Rift Block, is associated with anomalously shallow bathymetry, an atypical continental margin free-air gravity edge-effect anomaly, and an absence of seafloor spreading related magnetic anomalies. Off the central and western Wilkes Land margin, the COTZ extends ∼200 km from the shelf break and encompasses the magnetic anomaly previously interpreted as Chron 34y. It is clear, however, that this is not a seafloor spreading anomaly since oceanic crust was not emplaced in the Australia-Antarctic Basin until after 83 Ma. Integrated gravity and magnetic anomaly modelling indicates that the magnetic anomalies are likely to be caused by ridges of serpentinized mantle peridotites exhumed during rifting. Process-oriented gravity modelling indicates that the Wilkes Land margin lithosphere is characterized by a relatively high effective elastic thickness (Te) of ∼30 km, whereas preliminary models of the southern Australian margin are characterized by a lower average Te of ∼15 km. This contrast between the two margins is interpreted to reflect changing lithospheric rigidity since breakup in the Late Cretaceous. Whereas the southern Australian margin was heavily sediment-loaded during the Late Cretaceous but largely sediment starved throughout the Tertiary, the Wilkes Land margin was less extensively sedimented during the Late Cretaceous and early Cenozoic but loaded by thick sediments from the Late Oligocene to Middle Miocene. This contrast in loading histories allows discrete estimates of Te to be constrained rather than average estimates. We interpret this to suggest that the Te of stretched lithosphere increases through time following rifting. © 2009 The Authors Journal compilation © 2009 RAS.